PENGEMBANGAN VIDEO INTERAKTIF BERBASIS EDPUZZLE PADA MODEL ASSURE DALAM MATA PELAJARAN FIKIH KELAS X MA HIDAYATUL INSAN PALANGKA RAYA - Miftahul Rahmah; Jasiah Jasiah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study is to describe the process of developing Edpuzzle-based interactive video lessons and to identify the factors underlying the development of the subject matter in the Jurisprudence class, in order to improve students' motivation and learning outcomes. Research and development (R&D) ASSURE model was the methodology used for the development. The research was conducted at MA Hidayatul Insan Palangka Raya with a sample size of 20 students of class X A. There are two steps taken in the media validation process, namely media validation and material validation. Data sources were obtained through documentation studies, observation, interviews, and questionnaires. The results showed that media feasibility was 76%, material feasibility was 80%, and student response to the use of edpuzzle-based interactive video learning materials was 87%. Thus, it can be said that the edpuzzle-based interactive learning video developed is feasible to use and can increase students' interest in learning Jurisprudence.